PENGALAMAN MENARIK KETIKA MEMPELAJARI HADIS QUDSI: (Studi Fenomenologi pada Grup Hadits Qudsi Muslimah) - Yuhadi, Irfan; Nurul Budi Murtini, Nurul Budi Murtini (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2025)
An interesting experience refers to a pleasurable and meaningful event encountered by an individual. Hadith Qudsi is a type of hadith narrated by the Prophet Muhammad (peace be upon him) from Allah Almighty, and is also known as “rabbani” or divine hadith. The informants selected in this study were members of the Muslimah Hadith Qudsi Group. The purpose of this study was to analyze and explore interesting experiences gained by the group members in learning Hadith Qudsi. The approach used in this study was qualitative with a phenomenological study design. The findings revealed several interesting experiences among the participants while learning Hadith Qudsi, including: (1) gaining privileged knowledge, (2) being motivated to study history, (3) gaining abundant benefits from hadith, (4) enhancing obedience, (5) fostering the desire to regularly perform sunnah practices, (6) attaining peace of mind, (7) developing greater acceptance of divine destiny, (8) being motivated to self-improve, (9) feeling more comfortable interacting with others, (10) finding solutions to daily problems, (11) obtaining knowledge to teach their children, (12) gaining material for da'wah.